2020
DOI: 10.7150/ijms.43986
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Proliferation and Migration in Wound Healing by Phytochemicals: Evidence for a Novel Synergic Outcome

Abstract: Wound-healing is a dynamic skin reparative process that results in a sequence of events, including inflammation, proliferation, and migration of different cell types as fibroblasts. Fibroblasts play a crucial role in repairing processes, from the late inflammatory phase until the fully final epithelization of the injured tissue. Within this context, identifying tools able to implement cell proliferation and migration could improve tissue regeneration. Recently, plants species from all over the world are coming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 57 publications
3
95
0
2
Order By: Relevance
“…Our results confirmed the relationship between antioxidant activity due to the presence of bioactive phenolic compounds and cell proliferation, as reported by other studies [ 59 , 60 ]. In particular, this study further highlights that a proactive use of waste to ameliorate regenerative and antioxidant processes can be associated with a wide range of final usage.…”
Section: Resultssupporting
confidence: 93%
“…Our results confirmed the relationship between antioxidant activity due to the presence of bioactive phenolic compounds and cell proliferation, as reported by other studies [ 59 , 60 ]. In particular, this study further highlights that a proactive use of waste to ameliorate regenerative and antioxidant processes can be associated with a wide range of final usage.…”
Section: Resultssupporting
confidence: 93%
“…About 14–25% of diabetic patients have the complication of foot ulcer. The fibroblast cells-based wound scratch assay is one of the inexpensive and well-recognized techniques to understand the wound-healing efficiency of natural products [ 41 ]. There are plenty of plant extracts playing an astonishing role in accelerating the healing process.…”
Section: Resultsmentioning
confidence: 99%
“…The authors also highlighted that the synergistic effects could target multiple levels of different pathways and emphasised on the synergy among pure compounds as a method of new drug discovery. More interestingly, a recent study by Addis et al 57 demonstrated the synergistic effect of waste extract from different medicinal plants in improving fibroblast proliferation and migration which otherwise had been reported to have inhibitory effect on cancer cell Figure 7. Graphical summary of the effects of BLE on methylglyoxal metabolism.…”
Section: Discussionmentioning
confidence: 97%